Saudi Students’ Perceptions Towards the Effectiveness of Code-Switching in EFL Online Classes - Algethami, Abeer (International Journal of Linguistics and Translation Studies, 2025)
The COVID-19 pandemic significantly transformed the education field worldwide, shifting the teaching-learning process from traditional face-to-face classrooms to online learning environments. However, online learning often lacks essential elements that facilitate an effective teaching process, such as physical interactions, gestures, body language, and facial expressions. Consequently, teachers struggled to connect with students and subsequently adopted code-switching (CS) which involves alternating between students’ first language (L1) and the foreign language (FL) in English language classrooms. This study examines EFL students’ perceptions of the effectiveness of CS in online classes. A quantitative research approach was employed, and data were collected via a web-based questionnaire completed by 72 third-year students who had completed English language courses online. The findings indicate that most undergraduate students had positive perceptions of CS in online English classes. The study provides the reasons for employing CS and its role in enhancing the learning process in virtual classrooms. However, the study’s limitations highlight the need for further investigation in future research.